Aggressive use of prophylactic cerebrospinal fluid drainage to prevent spinal cord ischemia during thoracic endovascular aortic repair is not supportive. (5th September 2022) - Seike, Yoshimasa; Fukuda, Tetsuya; Yokawa, Koki; Koizumi, Shigeki; Masada, Kenta; Inoue, Yosuke; Matsuda, Hitoshi
Abstract: OBJECTIVES: We investigated whether prophylactic preoperative cerebrospinal fluid drainage (CSFD) was effective in preventing spinal cord ischemia (SCI) during thoracic endovascular aortic repair of degenerative descending thoracic aortic aneurysms, excluding dissecting aneurysms. METHODS: We retrospectively reviewed the medical records of patients who underwent thoracic endovascular aortic repair involving proximal landing zones 3 and 4 between 2009 and 2020. RESULTS: Eighty-nine patients with preemptive CSFD [68 men; median (range) age, 76.0 (71.0–81.0) years] and 115 patients without CSFD [89 men; median (range) age, 77.0 (74.0–81.5) years] were included in this study. Among them, 59 from each group were matched based on propensity scores to regulate for differences in backgrounds. The incidence rate of SCI was similar: 8/89 (9.0%) in the CSFD group and 6/115 (5.2%) in the non-CSFD group ( P  = 0.403). Shaggy aorta (odds ratio, 5.13; P  = 0.004) and iliac artery access (odds ratio, 5.04; P  = 0.005) were identified as positive predictors of SCI. Other clinically important confounders included Adamkiewicz artery coverage (odds ratio, 2.53; P  = 0.108) and extensive stent graft coverage (>8 vertebrae) (odds ratio, 1.41; P  = 0.541) were not statistically significant. Propensity score matching yielded similar incidence of SCI: 4/59 (6.8%) in the CSFD group and 3/59 (5.1%) in the non-CSFD group ( P  = 0.697). CONCLUSIONS: Aggressive use of prophylactic CSFD was not supportive in patients without complex risks of SCI. Abstract : Spinal cord ischemia (SCI) after thoracic endovascular aortic repair (TEVAR) for degenerative descending thoracic aortic aneurysms (TAA) still occurs at a significant rate [1, 2].